Audit indicators and financial performance of manufacturing firms in Nigeria - Ehiedu, Victor Chukwunweike; Toria, Gladys (Linguistics and Culture Review, 2021)
This study investigated audit Indicators and financial performance of manufacturing firms in Nigeria during the period 2003-2020 (18 years). The researcher used three firms Unilever Nigeria Plc., Beta Glass Plc. and Meyer Plc. The dependent variable was measured with earnings per share (EPS), while the independent variables were measured with auditor’s independence (AUIND), Audit Firm Size (AUSZ), Audit Committee (AUCMT), audit committee financial expertise (AUCFE). Time-series data were used and the researcher obtained it from the annual report and account of the firms under study. The estimation technique was Ordinary least square (OLS), normality, serial correlation, and heteroskedasticity test was carried out with the aid of E-views 9 statistical package. The study found that audit committee (AUCMT) and audit committee financial expertise (AUCFE) have a significant impact on earnings per share of Unilever Nigeria Plc as the p-value t-statistics is below 5% significant level. Also, the Audit Committee (AUCMT), audit independence (AUIND) and audit committee financial expertise (AUCFE) have a significant impact on earnings per share of Beta Glass Plc and Meyer Plc as the p-value t-statistics are below 5% significant level. Globally the p-value of the three manufacturing firms understudy is below 5% significant level.